Native Isolation of 3×HA‐Tagged Protein Complexes to Characterize Protein‐Protein Interactions. Issue 2 (4th February 2021) - Lim, JiaWen; Iftner, Thomas; Simon, Claudia
Abstract: Co‐immunoprecipitation (Co‐IP) is a straightforward method that is widely used in studying direct protein‐protein interactions in physiological environments. This technique is based on the antigen‐antibody interaction: the protein of interest (bait) is captured by a specific antibody, followed by antibody‐bait precipitation. The proteins interacting with the bait protein (prey) co‐precipitate with the antibody‐bait complex from a cell lysate as an antibody‐bait/prey complex. Nowadays, a variety of surface‐functionalized materials with antibodies immobilized on agarose or magnetic beads are available, replacing the precipitation of antibodies and simplifying the application. However, unspecific binding of cellular proteins to matrix surfaces and/or antibodies has become a common issue. Unspecific binding that leads to false‐positive signals and a high background can hamper further analysis. Our protocol describes a strategy to tremendously reduce unspecific background when isolating native proteins and protein complexes. Instead of eluting our samples under denaturing conditions, we elute triple hemagglutinin (3×HA)‐tagged bait/prey complexes in their native form with a competitive peptide simulating the 3×HA tag of the bait protein. Matrix‐unspecific interacting proteins and Co‐IP antibodies remain on the matrix instead of being eluted under conventionally applied denaturing conditions. We optimized the elution by altering incubation time, eluent concentration, and temperature. These improvements result in more pure proteins. This strategy not only reduces background in SDS‐PAGE and western blot but also allows complex characterization in vitro. © 2021 Wiley Periodicals LLC.